1989
DOI: 10.1126/science.2916128
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Transforming Growth Factor α in Psoriatic Epidermis

Abstract: Transforming growth factor alpha (TGF-alpha) is produced by and required for the growth of epithelial cells and is angiogenic in vivo. Since epidermal hyperplasia and angiogenesis are hallmarks of psoriasis, TGF-alpha gene expression was analyzed in epidermal biopsies of normal and psoriatic skin. TGF-alpha messenger RNA and protein are much more abundant in lesional psoriatic epidermis than in normal-appearing skin of psoriatic patients or in normal epidermis. In contrast, messenger RNA levels of transforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
254
0
7

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(270 citation statements)
references
References 41 publications
9
254
0
7
Order By: Relevance
“…Several reports have implicated an increase in EGF receptors with epidermal tumorigenesis (Yamamoto et al, 1986;Ozanne et al, 1986). In addition, it was recently reported that psoriatic epidermis contained higher levels of TGF-t~ than normal skin, suggesting that overexpression of TGF-t~ might contribute to hyperproliferative diseases of the skin (Gottlieb et al, 1988;Elder et al, 1989). This hypothesis is an attractive one, although it remains to be shown whether the increase in TGF-o~ in psoriasis is causal or consequential.…”
Section: Molecular Controls Of Epidermal Growth and Differentiation: mentioning
confidence: 94%
See 1 more Smart Citation
“…Several reports have implicated an increase in EGF receptors with epidermal tumorigenesis (Yamamoto et al, 1986;Ozanne et al, 1986). In addition, it was recently reported that psoriatic epidermis contained higher levels of TGF-t~ than normal skin, suggesting that overexpression of TGF-t~ might contribute to hyperproliferative diseases of the skin (Gottlieb et al, 1988;Elder et al, 1989). This hypothesis is an attractive one, although it remains to be shown whether the increase in TGF-o~ in psoriasis is causal or consequential.…”
Section: Molecular Controls Of Epidermal Growth and Differentiation: mentioning
confidence: 94%
“…TGF-o~ differs from EGF in that it is synthesized by keratinocytes both in vitro and in vivo (Coffey et al, 1987;Gottlieb et al, 1988;Elder et al, 1989). Since epidermal cells autoregulate their own growth via TGF-tx production, it is perhaps not surprising to find that such control can go awry, leading to uncontrolled growth.…”
Section: Molecular Controls Of Epidermal Growth and Differentiation: mentioning
confidence: 99%
“…TGF␣, which is the natural ligand for EGF receptors present on keratinocytes, is overexpressed in psoriatic skin (9). The increased production of TGF␣ may be an important contribution to keratinocyte hyperplasia, because TGF␣ is a potent mitogen for keratinocytes (9).…”
Section: Discussionmentioning
confidence: 99%
“…12(S)-HETE may play a significant role in the pathogenesis of some epidermal and epithelial inflammation, because a markedly elevated 12(S)-HETE level was found in psoriatic plague (7). In psoriatic lesions, overexpression of epidermal growth factor (EGF) receptors (8), transforming growth factor-␣ (TGF␣) (9), and 12(S)-lipoxygenase (10) has been reported.…”
mentioning
confidence: 99%
“…In vitro studies show that lymphocytes interact with keratinocytes through leukocyte function-associated antigen-1 (LFA-1)-intercellular adhesion molecule-1 (ICAM-1) (Dustin et al, 1988). The interaction between keratinocytes, local antigen-presenting cells, and T lymphocytes likely initiates and maintains psoriatic lesions via the induction of cytokines, chemokines, and growth factors such as transforming growth factor-␣ (Austin et al, 1999;Elder et al, 1989;Goebeler et al, 1998;Nickoloff, 1991). Locally derived growth factors also contribute to epidermal hyperplasia in conditions other than psoriasis, for example, in wound healing (Stenn and Malhotra, 1992) and cancer (Gottlieb et al, 1988).…”
mentioning
confidence: 99%